Brain metastasis in a patient with multiple malignancies. Issue 2 (February 2021) - Robinson, Kevlin; Zerfoss, Cindy; Nicholas, Joyce; Rolfs, Jenna
Abstract : ABSTRACT: Brain metastases originate from other primary cancers within the body, most commonly lung, breast, and melanoma. Because patients with brain metastasis, stroke, or intracranial hemorrhage may present with similar acute neurologic symptoms, clinicians must have a high suspicion for brain metastasis and perform an immediate workup to rule out life-threatening conditions. This case report focuses on the clinical symptoms, diagnostics, and treatment options for brain metastasis in a patient with multiple malignancies.